International business scholarship AIB fellows on the first 50 years and beyond - Boddewyn, J. J. (Emerald, 2008)
The AIB Fellows Group includes top researchers, educators, and administrators in the IB field. Most of its 60 members have contributed to this edited volume as authors, co-authors and reviewers, including such noteworthy scholars as John Dunning, Alan Rugman and Yair Aharoni, among many others.Its chapters examine aspects of the growth of the field, evaluate our present state of knowledge and outline future lines of research. They cover the growth of several functional areas (marketing, advertising, finance, etc.), review problems of methodological rigor in IB research, trace the history and evolution of IB studies and their likely future trajectories, raise ethical and moral issues about IB practices and evaluate the impact of major theories on IB studies. A couple of chapters cover the history of international business and of the AIB Fellows Group. Altogether, this book provides a benchmark of where IB knowledge stands today and will grow in coming years.
Includes indexes.
Keywords: Business & Economics -- International -- General.; International business.; International business enterprises.; elektronické knihy; electronic books